Serum carcinoembryonic antigen tends to decrease in poorly-differentiated colorectal cancer - Ester Morina Silalahi; Lukman Hakim Zain; Rustam Effendi (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUND Carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 are tumor markers for colorectal cancer (CRC), both having prognostic value. According to the Colorectal Working Group of the American Joint Committee on Cancer, increases in CEA and CA 19-9 levels of >5 µg/l and > 37 U/ml, respectively, are considered abnormal. Increased serum CEA may be encountered in postoperative CRC patients from recurrences or metastases. There are no research data in Indonesia on the characteristics of CEA and CA 19-9 levels according to preoperative CRC cellular differentiation. The objective of this study was to determine differences in serum CEA and CA 19-9 levels according to CRC cellular differentiation. METHODSThis was a cross-sectional study conducted on 40 CRC subjects from July 2012 until May 2013. Determination of serum CEA and CA 19-9 levels and histopathological (cellular) differentiation grades in CRC biopsies was done in all subjects. RESULTS The study involved forty CRC patients, consisting of 22 males and 18 females, with mean age of 51.93 ± 11.63 years, CEA levels of 51.93 ± 84.07 ng/ml and CA 19-9 levels of 33.81 ± 62.39 U/ml. Carcino-embryonic antigen levels tended to decrease with decreasing CRC histopathological grade, while CA 19-9 levels increased in well-differentiated CRC. However, both relationships were statistically not significant (with p=0.314 and p=0.787, respectively). CONCLUSIONS Carcinoembryonic antigen (CEA) levels tend to decrease with decreasing histopathological grade of CRC, and CA 19-9 levels tend to increase in well-differentiated CRC.